Adaptive Tracking Control for Tethered Aircraft Systems With Actuator Nonlinearities and Output Constraints - Zhang, Fan; Song, Mengshi; Huang, Bingxiao; Huang, Panfeng (IEEE transactions on aerospace and electronic systems, 2024)
This article addresses the adaptive tracking control problem of tethered aircraft systems subject to airflow disturbances, output constraints, and actuator nonlinearities of saturation, dead zone, and fault. By combining the nonlinear reconstruction model of the actuator, composed of the ideal and actual reconstruction forms, with the auxiliary system containing a saturation function, the controller design difficulty incurred by actuator nonlinearities is solved. Meanwhile, to guarantee the normal operation of the system under input saturation and output constraints with excessively large initial output values, the constraint function and the auxiliary system building the bridge between input saturation and output constraints are simultaneously introduced to modify the output constraint boundary. Furthermore, considering airflow disturbances, uncertainties, and actuator faults in systems, extended state observers are designed to estimate the lumped disturbance. Then, an adaptive tracking controller is proposed to guarantee the outputs meet the modified constraints, and all signals in the closed-loop system are bounded. Finally, the simulation results demonstrate the effectiveness of the proposed controller.